Current trends in natural preservatives for fresh sausage products - Strashynskyi, Igor; Pasichnyi, Vasyl; Ryshkanych, Roman (My University, 2021)
Natural preservatives from bacteria, plants and animal currently in use in fresh sausage manufacture were investigated. Plant-derived antimicrobials could increase the shelf-life of fresh sausages and in some cases also decrease lipid oxidation and decrease colour loss. The quality of fresh sausages is of major importance since the shelf-life of the products depends on this aspect. Spoilage of food involves a complex process and excessive amounts of food may be lost, which results in high economic losses or even pose health hazards. Spoilage of fresh sausages may result in changes in the sensory (colour, odour, flavour, texture) characteristics of the product which may be unacceptable for consumers.
Keywords: кафедра технології м’яса і м’ясних продуктів; natural preservative; quality of fresh sausages; plant-derived antimicrobials